The Readiness of Islamic Religious Education Teachers in Implementing the Merdeka Curriculum - Taufik Mustofa; Agus Ruswandi; Ahmad Hapidin; Uus Ruswandi; Ferianto Ferianto; M Makbul (AL-ISHLAH: Jurnal Pendidikan, 2023)
Despite the rollout of the Merdeka Curriculum, its adoption in some madrasas remains incomplete. This study explores the readiness of PAI (Islamic Religious Education) instructors in Madrasah Tsanawiyah and Madrasah Aliyah to implement the Curriculum Merdeka, focusing on the challenges posed by limited socialization opportunities and a general lack of motivation among teachers. Utilizing a qualitative research design, this study employed descriptive methodologies to gather insights. Data was collected through questionnaires from 36 respondents and analyzed using a systematic approach involving data reduction, data display, and verification processes. The findings reveal significant gaps in the readiness of PAI teachers to effectively implement the Curriculum Merdeka. Only 16.67% of teachers demonstrated a high level of awareness of the curriculum’s content. About 11.11% of the instructors showed a deep understanding of its fundamental principles and could distinguish it from the previous curriculum. Furthermore, only 16.67% had access to the necessary curriculum and learning documents, and a mere 11.11% possessed adequate learning resources to apply the Curriculum Merdeka effectively. This study underscores the need for enhanced training and resource allocation to ensure the successful adoption of the Curriculum Merdeka in madrasas.